In-situ determination of dispersion and resolving power in simultaneous multiple-angle XUV spectroscopy - Zastrau, U; Hilbert, V; Brown, C; Döppner, T; Dziarzhytski, S; Förster, E; Glenzer, H; Göde, S; Gregori, G; Harmand, M; Hochhaus, D; Laarmann, T; et al. (2011)
We report on the simultaneous determination of non-linear dispersion functions and resolving power of three flat-field XUV grating spectrometers. A moderate-intense short-pulse infrared laser is focused onto technical aluminum which is commonly present as part of the experimental setup. In the XUV wavelength range of 10-19 nm, the spectrometers are calibrated using Al-Mg plasma emission lines. This cross-calibration is performed in-situ in the very same setup as the actual main experiment. The results are in excellent agreement with ray-tracing simulations. We show that our method allows for precise relative and absolute calibration of three different XUV spectrometers. © 2011 IOP Publishing Ltd and SISSA.